2016
DOI: 10.18632/oncotarget.12899
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of laparoscopic-assisted synchronous bowel anastomoses for synchronous colorectal cancer: initial clinical experience

Abstract: The primary aim of this study was to explore the safety and feasibility of laparoscopic-assisted synchronous bowel anastomoses (LSBA) for synchronous colorectal cancer (SCRC). All patients who underwent LSBA for SCRC were retrospectively reviewed and analyzed for clinical and pathological features, technical feasibility and short-term as well as long-term oncological outcomes. Between July 2008 and January 2012, a series of 11 consecutive SCRC patients underwent LSBA. Six patients underwent laparoscopic-assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…As a surgical approach, laparoscopic surgery has significant advantages in terms of short-term outcomes including early recovery and no disadvantageous long-term outcomes. According to recent reports, laparoscopic surgery has been used in SCRCs [ 6 ], but these reports noted that controversy remains concerning operative procedures for multiple segmental resections and for total or subtotal colectomy. We report the case who presented with quadruple synchronous advanced cancers arising from the colon, which were successfully treated with laparoscopic two-segment colectomy.…”
Section: Introductionmentioning
confidence: 99%
“…As a surgical approach, laparoscopic surgery has significant advantages in terms of short-term outcomes including early recovery and no disadvantageous long-term outcomes. According to recent reports, laparoscopic surgery has been used in SCRCs [ 6 ], but these reports noted that controversy remains concerning operative procedures for multiple segmental resections and for total or subtotal colectomy. We report the case who presented with quadruple synchronous advanced cancers arising from the colon, which were successfully treated with laparoscopic two-segment colectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment variables include extended surgical resection with anastomosis when there are multiple tumors in the colon. It is also possible to perform segmental resections with anastomosis if the case allows [16, 17]. Among the complications of performing segmental resections are ileus and stenosis, while performing an extended resection, complications such as ileus, intestinal leakage, intra-abdominal collections, and mesenteric artery thrombosis can be expected [6, 16].…”
Section: Discussionmentioning
confidence: 99%
“…When SCRC are located in distant colonic segments, some authors suggest total or subtotal colectomy to remove synchronous tumours or polyps eventually undetected at preoperative imaging and to prevent the development of metachronous neoplasms[ 14 , 15 ]. In the same circumstances, other authors suggest more conservative surgical strategies, with resection of two intestinal segments (either open or laparoscopic-assisted)[ 13 , 16 - 18 ] and two anastomoses, seemingly resulting in a higher risk of anastomotic dehiscence[ 6 ].…”
Section: Synchronous Colorectal Carcinomamentioning
confidence: 99%
“…Length of stay was seven (5-10) days, overall 30-day morbidity was 36% without anastomotic leaks or fistulas, and 30-day mortality was 3%. Li et al[ 18 ] examined a personal series of 11 patients and 52 adjunctive patients collected from six previous reports of the literature who underwent laparoscopic-assisted combined bowel anastomoses for SCRC, and concluded that combined bowel anastomoses are potentially feasible and safe procedures for SCRC when performed by experienced surgeons.…”
Section: Synchronous Colorectal Carcinomamentioning
confidence: 99%
See 1 more Smart Citation